"Connections above and beyond": Information, translation, and community boundaries in LibraryThing and Goodreads. (22nd February 2019) - Worrall, Adam
Abstract : The connections and contexts surrounding information shared in social settings must be accounted for, and this is particularly true for online communities that are information‐centric. This article presents a mixed‐methods study of LibraryThing and Goodreads, which have characteristics of information‐centric online communities and social digital libraries, with attention to their roles as boundary objects, users' information values, and information behavior, and other boundaries and boundary objects at play. Content analysis of messages, a survey of users, and qualitative interviews show LibraryThing and Goodreads help establish community and organizational structure; support sharing of information values; and facilitate the building and maintenance of social ties. Translation of meanings and understandings within and between communities is a key activity in these roles. Online communities and social digital libraries should highlight translation processes and resources; provide user profiles and off‐topic spaces and encourage their use; take a sociotechnical approach to tailor technology and community features to the right audiences; and facilitate the establishment of shared structure, values, and ties and the work of boundary spanners. Further implications exist for research on and theorizing of information‐centric online communities, boundaries, and boundary objects as part of the sociotechnical infrastructure surrounding online information sharing.